Comparison of Teaching Planning in Learning Activities: Conventional and Innovative Approaches in the Era of Educational Transformation - Inayatul Mutmainnah; Jusniati. H; Suaebah; Saprin; Yuspiani (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2025)
This study examines the comparison between conventional and innovative instructional planning models in the context of educational transformation. The objectives are (1) to describe the characteristics of various instructional planning models, (2) to analyze their differences and similarities, and (3) to evaluate the effectiveness of new approaches such as the Merdeka Curriculum, Project-Based Learning, and differentiated instruction in improving the quality of teaching and learning processes. The research method includes a literature review and comparative analysis of various instructional planning approaches. The findings indicate that (1) modern instructional planning must be student-centered, (2) competency- and character-based, and (3) make optimal use of technology. Innovative models prove to be more effective due to their flexibility, participatory nature, and ability to adapt to student diversity through active learning methods such as Project-Based Learning, Differentiated Instruction, and Backward Design. New approaches like the Merdeka Curriculum have demonstrated positive impacts on learning quality by fostering active, collaborative, and contextual learning environments, thereby promoting the development of 21st-century skills and character values in a sustainable manner. The study recommends the need for professional teacher training, strengthening educators' capacity in designing innovative lesson plans, and policy support to enable the implementation of adaptive and relevant learning practices. Thus, instructional planning can serve as a key strategy in creating high-quality and transformative learning experiences.